Asymmetric apical hypertrophy: ten years experience. Issue 728 (June 1986) - Sakamoto, T.; Amano, K.; Hada, Y.; Tei, C.; Takenaka, K.; Hasegawa, I.; Takahashi, T.
Abstract : This paper reports 10 years experience of 31 patients with asymmetric apical hypertrophy, in whom left ventricular hypertrophy involved the apex exclusively and giant T wave inversion in the left precordial leads was the characteristic finding. This type of hypertrophic cardiomyopathy was observed predominantly in men over 40 years of age. Family history was negative and patients usually had no complaints. Left ventricular hypertrophy was evident by physical examination as in other forms of hypertrophic cardiomyopathy, but a systolic murmur was faint or absent and the second heart sound was frequently split. Electrocardiographic signs may fluctuate, and occasionally progression or regression occurs. Echocardiography including the two-dimensional method was essential for the diagnosis and left ventriculography was helpful for confirmation. To date complications have been infrequent and the prognosis seems good. The relation of asymmetric apical hypertrophy to other forms of hypertrophic cardiomyopathy is under investigation.